남부평야지 조기재배 적응 복합내병성 고품질 조생 벼 ‘조일’ - 남정권(Jeong Kwon Nam); 박현수(Hyun Su Park); 김기영(Ki Young Kim); 김보경(Bo Kyeong Kim); 조영찬(Young Chan Cho); 고재권(Jae Kwon Ko); 백만기(Man Kee Baek); 김정주(Jeong Ju Kim); 김우재(Woo Jae Kim); 신운철(Woon Chul Shin); 고종철(Jong Cheol Ko); 이점호(Jeom Ho Lee); et al. (Korean journal of breeding, 2018)
‘Joil’ is a multiple disease resistant early maturing rice cultivar with high grain quality. ‘Joil’ was derived from a single cross between ‘Unbong37’ (cultivar name ‘Unmi’) and ‘HR23156-26-2-3-5’. ‘Unmi’ is an early maturing rice cultivar with high grain quality and resistance to rice blast and stripe virus. ‘HR23156-26-2-3-5’ is an early maturing elite rice line with lodging resistance and cold tolerance. ‘Joil’ was selected through the pedigree method, yield trials, and local adaptability tests. ‘Joil’ was an early maturing rice. The heading date of ‘Joil’ was July 16 in early transplanting cultivation, which was 2 days later than that of ‘Jopyeong’. ‘Joil’ was a lodging resistance rice with a short culm and showed better tolerance to viviparous germination than that of ‘Jopyeong’. ‘Joil’ was a multiple disease resistant rice with resistance against rice blast, bacterial blight, and stripe virus. ‘Joil’ showed higher yield in both early and late-transplanting cultivations than those of the standard rice cultivars ‘Jopyeong’ and ‘Geumo’. ‘Joil’ had enhanced grain quality under high temperature ripening conditions in early transplanting cultivation. The cooked rice had good grain appearance and taste attributes, and this cultivar had a higher head rice ratio than that of ‘Jopyeong’. ‘Joil’, a multiple disease resistant early maturing rice cultivar with high grain quality, would be suitable for early transplanting cultivation in the southern plain area (Registration No. 6792). KCI Citation Count: 8